2003
DOI: 10.1029/2002jd002848
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variations of monthly and seasonal normalized difference vegetation index (NDVI) in China from 1982 to 1999

Abstract: In this paper, we analyzed interannual variations of normalized difference vegetation index (NDVI) and their relationships with climatic variables (temperature and precipitation) and human activity in China between 1982 and 1999. Monthly and seasonal NDVI increased significantly at both the country and biome scales over the study period. NDVI shows the largest increase (14.4% during the 18 years and a trend of 0.0018 yr−1) over 85.9% of the total study area in spring and the smallest increase (5.2% with a tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
361
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(390 citation statements)
references
References 34 publications
22
361
1
6
Order By: Relevance
“…p values were based on one-tailed hypothesis, and "*", "**", and "***" are for p-values less than 0.1, 0.05, and 0.01, respectively. Vegetation indices in China increased significantly until the mid-1990s, after which the trend was weakened or even reversed according to previous reports [50,52,62]. Similar changes were observed in North America [63].…”
Section: Regression Of Annual Averaged Evi On Growing Season Length Asupporting
confidence: 70%
See 1 more Smart Citation
“…p values were based on one-tailed hypothesis, and "*", "**", and "***" are for p-values less than 0.1, 0.05, and 0.01, respectively. Vegetation indices in China increased significantly until the mid-1990s, after which the trend was weakened or even reversed according to previous reports [50,52,62]. Similar changes were observed in North America [63].…”
Section: Regression Of Annual Averaged Evi On Growing Season Length Asupporting
confidence: 70%
“…Nevertheless, the rainfall increase in the winter and spring may advance the starting day of DSRTHC, which was suggested by former study that in the water limited areas increasing precipitation in preceding months can advance the growing season [68]. In addition, the increased spring temperature may advance the starting day of DSRTHC and eventually lead to the EVI increase in the spring (Tables 2 and 3) [62,69]. Similarly, a weaker increase in the winter rainfall and spring temperature led to a small increase in the spring DSRTTP EVI.…”
Section: Growing Seasonal Length and Climate Explained The Changes Inmentioning
confidence: 97%
“…Previous studies have demonstrated that the influence of climate change on vegetation growth may have a time lag (Piao et al, 2003;Udelhoven et al, 2009). In the HYR region, the grassland NDVI reaches the maximum mainly in August.…”
Section: Restrend Analysismentioning
confidence: 99%
“…The study of the response of vegetation growth to climate change on regional, continental, and global scales is receiving increasing attention (Myneni et al, 1997;Zhou et al, 2001;Lucht et al, 2002;Piao, 2003;Piao et al, 2006aPiao et al, , 2014Anderson et al, 2010;Peng et al, 2011;Wu et al, 2012). Recent research has indicated a weakening relationship between inter-annual temperature variability and northern vegetation activity over the past three decades (Piao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change can significantly affect vegetation activity (Myneni et al, 1997;Piao, 2003;Badeck et al, 2004;Garrity et al, 2011;Peng et al, 2011;Chen and Chen, 2013;Wu and Liu, 2013) and influence the terrestrial carbon cycle. Previous studies have reported both positive and negative influences of climate change on vegetation growth.…”
Section: Introductionmentioning
confidence: 99%